Trends of Homicidal Deaths in Gwalior Region: An Autopsy Based Retrospective Study - Saxena , D; Juglan , S; Tomar , J S; Varun , A (Journal of Indian Academy of Forensic Medicine, 2023)
In the present study homicidal victims were autopsied to determine the profile and pattern of injuries sustained. The study was conducted  at the department of Forensic Medicine and Toxicology Gajra Raja Medical College Gwalior to know the incidences and trends of the  homicides, taking it as the first step in the prevention of crime. During the above said period of 2 years a total number of 4291 cases were  autopsied out of which 107 cases were homicidal in nature. The study shows that the overall number of people who suffered a violent death  had increased which were 45 cases in the year 2020 to 62 cases in 2021. Majority of victims fall in the age group of 21-30 yrs, 37 cases  (34.57%). Sex wise distribution showed male preponderance with 70 cases. In our study death due to firearm injuries were the most  common form of assassination practiced (42.9%) followed by blunt weapon injuries (28.97), sharp weapon injuries (15.88%) and the  number of asphyxia deaths were less (12.14%). Motive was financial matter (30.84%), family disputes (22.42%) arguments (19.62 %),  land disputes (15.88 %). The incidence of infidelity and unknown motives was reported in (7.47 %) and (3.73 %) respectively. The present  study was conducted over the period of two years from January 2020 to December 2021. The data collected includes all reported unnatural  deaths from the urban and rural areas of the district on which autopsies were conducted at the mortuary of Department of Forensic  Medicine and Toxicology, Gajra Raja Medical College Gwalior.
Keywords: Homicidal deaths; Weapon; Violent deaths; Firearm injuries